2019
DOI: 10.1080/09273948.2019.1662059
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Diagnosis of Anterior Segment Inflammation Related to Cytomegalovirus in Immunocompetent African, Asian, and Caucasian Patients

Abstract: To report the clinical features and treatment outcomes in immunocompetent patients with anterior segment inflammation (ASI) related to human cytomegalovirus (HCMV) depending on their ethnic origin. Material and Methods: Multicenter retrospective study of 38 patients with at least one test, either HCMV-positive PCR or GWc. Results: Features of Posner-Schlossman syndrome were observed in 50% of the eyes, Fuchs heterochromic iridocyclitis in 13% of the eyes, chronic nonspecific anterior uveitis in 21% of the eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…In the treatment of CMV infections, a study found that ganciclovir topical ointment is effective in preventing relapses of CMV-associated uveitis (19,21), whereas oral valganciclovir appears to be more effective in acute episodes (22,23). Another study showed that oral valganciclovir is effective in treating acute symptoms and in reducing the frequency of disease recurrence (24). It was also reported that if anti-CMV therapy can effectively control cytomegalovirus replication, antiglaucoma surgery is rarely required (5).…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of CMV infections, a study found that ganciclovir topical ointment is effective in preventing relapses of CMV-associated uveitis (19,21), whereas oral valganciclovir appears to be more effective in acute episodes (22,23). Another study showed that oral valganciclovir is effective in treating acute symptoms and in reducing the frequency of disease recurrence (24). It was also reported that if anti-CMV therapy can effectively control cytomegalovirus replication, antiglaucoma surgery is rarely required (5).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the relative prevalence of CMV- related AU presentations, we showed in our own series of 38 patients that features of Posner-Schlossman syndrome were observed in 50% of the eyes, Fuchs heterochromic iridocyclitis in 13% of the eyes, chronic nonspecific AU in 21% of the eyes, and corneal endotheliitis in 18% of the eyes [ 94 ]. Diagnosis usually relies on aqueous fluid viral PCR or Goldmann-Witmer coefficients positive for CMV [ 2 , 87 , 88 , 95 ].…”
Section: Misdiagnoses Among Uveitis/ Anterior Segment Inflammation En...mentioning
confidence: 99%
“…[ 7 ] Furthermore, oral ganciclovir, valganciclovir, or intravitreal ganciclovir have shown satisfactory responses in patients. [ 9 ] Some patients even have relapses after discontinuation of therapy. [ 9 ] A study among Japanese patients suggests a close association of HLA-Bw54 with PSS, thereby indicating an immune-genetic role being played here.…”
mentioning
confidence: 99%
“…[ 9 ] Some patients even have relapses after discontinuation of therapy. [ 9 ] A study among Japanese patients suggests a close association of HLA-Bw54 with PSS, thereby indicating an immune-genetic role being played here.…”
mentioning
confidence: 99%